Loss‐of‐Function Mutations in the ALPL Gene Presenting with Adult Onset Osteoporosis and Low Serum Concentrations of Total Alkaline Phosphatase. (7th January 2020) - Alonso, Nerea; Larraz‐Prieto, Beatriz; Berg, Kathryn; Lambert, Zoe; Redmond, Paul; Harris, Sarah E; Deary, Ian J; Pugh, Carys; Prendergast, James; Ralston, Stuart H
ABSTRACT: Hypophosphatasia (HPP) is a rare inherited disorder characterized by rickets and low circulating concentrations of total alkaline phosphatase (ALP) caused by mutations in ALPL . Severe HPP presents in childhood but milder forms can present in adulthood. The prevalence and clinical features of adult HPP are poorly defined. The aim of this study was to evaluate the prevalence and clinical significance of low serum total alkaline phosphatase (ALP) levels in a clinic‐based population of adult osteoporotic patients. We searched for patients with low ALP in a cohort of 3285 patients referred to an osteoporosis clinic over a 10‐year period and performed mutation screening of ALPL in those with low ALP (≤40 U/L) on two or more occasions. These individuals were matched with four clinic controls with a normal ALP. We also evaluated the prevalence of low ALP and ALPL mutations in 639 individuals from the general population from the same region. We identified 16/3285 (0.49%) clinic patients with low ALP and 14 (87.5%) had potentially pathogenic variants in ALPL . Eight of these individuals were heterozygous for mutations previously described in HPP and 2 were heterozygous for novel mutations (p.Arg301Trp and p.Tyr101X). These mutations were not found in clinic controls or in the general population. Eight patients with low ALP, including 4 with ALPL mutations, were treated with bisphosphonates for an average of 6.5 years. In these individuals, the rate of fractures during treatment was comparable to that in normal ALP clinic controls who were treated with bisphosphonates. We conclude that heterozygous loss‐of‐function mutations in ALPL are common in osteoporosis patients with low ALP. Further studies are required to determine how best these individuals should be treated. © 2019 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.